2016
DOI: 10.1155/2016/6306984
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Acute Matriptase Inhibition in Hepatic Inflammatory Models

Abstract: Purpose. Dysfunction of matriptase-2 can be involved in iron regulatory disorder via downregulation of hepcidin expression. In the present study, we investigated the effects of 3-amidinophenylalanine-derived matriptase inhibitors on porcine hepatic inflammatory cell models. Methods. Hepatocyte-Kupffer cell cocultures (ratio of 2 : 1 and 6 : 1) were treated with four structurally related matriptase inhibitors at 50 μM. Cell cytotoxicity and relative expressions of IL-6 and IL-8 and the levels of hepcidin were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…The solutions of the inhibitors in phenol red free Williams' Medium E at 50 μM (in the case of MI-461, 1, 10, 30, and 50 μM) were prepared freshly prior to each experiment from the stock solutions. It was found that the selected inhibitors can be used at 50 μM concentration safely for 24 h (cell death rate was less than 5% in controls and in treated samples) in Hep mono-and HepK6 co-cultures (Pomothy et al 2016) using MTS assay and this concentration could be applied in further experiments to characterize the effects of MT-1/MT-2 modulation in our hepatic models for 24 h. After incubation with the inhibitors for 24 h, the mono-and co-cultures were washed twice with plain medium before being subjected to the subsequent procedures.…”
Section: Exposure Of Hep and Hepk6 Cells To Matriptase Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The solutions of the inhibitors in phenol red free Williams' Medium E at 50 μM (in the case of MI-461, 1, 10, 30, and 50 μM) were prepared freshly prior to each experiment from the stock solutions. It was found that the selected inhibitors can be used at 50 μM concentration safely for 24 h (cell death rate was less than 5% in controls and in treated samples) in Hep mono-and HepK6 co-cultures (Pomothy et al 2016) using MTS assay and this concentration could be applied in further experiments to characterize the effects of MT-1/MT-2 modulation in our hepatic models for 24 h. After incubation with the inhibitors for 24 h, the mono-and co-cultures were washed twice with plain medium before being subjected to the subsequent procedures.…”
Section: Exposure Of Hep and Hepk6 Cells To Matriptase Inhibitorsmentioning
confidence: 99%
“…An inhibition of MT-1 and MT-2 is also achieved by sulfonylated 3-amidinophenylalanine derivatives (Hammami et al 2012). The most potent analogues of this inhibitor-type contain an N-terminal dichloro-or dimethoxy-biphenyl-3-sulphonyl group and inhibit MT-1 in the low one-digit nanomolar range, whereas the best inhibition constants for MT-2 are close to 100 nM (Hammami et al 2012;Pomothy et al 2016). However, the effects of these combined MT-1/2 inhibitors on the compensation for iron homeostatic imbalances caused by dysregulated hepcidin production have not been elucidated yet.…”
Section: Introductionmentioning
confidence: 99%
“…ROS and cell viability were also measured by establishing the effects of 3,3 0 -diindolylmethane (DIM) antioxidant agent on HIEC-6 51 . Using MI-1900 and MI-1907, the extracellular hydrogen-peroxide production and release of pro-inflammatory cytokines such as IL-6 and IL-8 were monitored and it was confirmed that both compounds at 50 mM did not induce excessive oxidative or inflammatory responses in HIEC-6 similarly to other Phe(3-Am)-derived inhibitors such as MI-460 and 461 in hepatocytes-based cell cultures 52,53 .…”
Section: Discussionmentioning
confidence: 82%
“…The impact of several Phe(3-Am)-derived inhibitors was investigated on porcine intestinal epithelial cell line, IPEC-J2, hepatocyte mono-and hepatocyte-Kupffer cell co-cultures. It was found that 50 mM MI-432, 441, 460, and 461 did not exert any detrimental effects on cell viability of hepatocyte-Kupffer cell co-cultures 52 . In addition, a significant increase in hepcidin levels was detected in hepatocyte mono-and hepatocyte-Kupffer cell co-cultures after acute treatments 53 .…”
Section: Discussionmentioning
confidence: 93%
“… 120 Finally, compounds MI460 and CAS RN 944925–37–5 may also inhibit proinflammatory cytokines and block blood coagulation-related factors, respectively. 121 , 122 …”
Section: Bioassay and Structure–activity Relationship Data For Small mentioning
confidence: 99%